MODEL PEMBELAJARAN PENGALAMAN BERBANTUAN MULTIMEDIA PADA PEMBELAJARAN MENULIS TEKS NARASI SISWA KELAS VII SMP - Dian Pebriana Silalahi, - (2018)
Penelitianinidilatarbelakangiolehrendahnyakemampuanmenulisteksnarasisiswa di SMPN 44 Bandung.Karenadalamrendahnyakemampuanmenulistersebutdapatdibantudenganmenghadirkan media sebagaiperantara.Bantuan media ituseperti media, video, danteks yang dapatmembantumengatasipermasalahandalampembelajarankhususnyamenulis.Dalamhalinipembelajaranakanmenerapkan model pembelajaranpengalamanberbantuan multimedia padapembelajaranmenulisteksnarasi.Berdasarkanhaltersebut, penelitiakanmelihatprofilawal SMPN 44 Bandung, mengujikeefektifanpenerapan model pembelajaranpengalamanberbantua multimedia padapembelajaranmenulisteksnarasi. Tujuan dari penelitian ini yaitu untuk melihat keefektifan model pembelajaranpengalamanberbantuan multimediapadapembelajaranmenulisteksnarasi. Model inimenjadisalahsatu model pembelajaran yang dapatdigunakandalampembelajaranmenulisteksnarasi.Metodepenelitian yang digunakanadalaheksperimensemu/kuasidnegandesainnonequivalent control group design.Penelitianinimenggunakanduakelas, yaitukelaskontroldankelaseksperimendenganjumlahmasing-masingsebanyak 20 orang.Data dalampenelitianiniberupahasilteskemampuanmenulisteksnarasi.Hasilpenelitianmenunjukkanterdapatperbedaan yang signifikandalampembelajaranmenulisteksnarasidenganmenggunakan model pembelajaranpengalamanberbantuan multimedia. Hal ini, dibuktikandengannilai rata-rata prates danpascates di kelaskontroldaneksperimen. Nilai rata-rata prates di kelaseksperimensebesar 63, danpascatessebesar 70. Berbedadengan di kelaskontrol, nilai rata-rata prates di kelaskontrolsebesar 62,3, danpascates di kelaskontrolsebesar 64,4. Data tersebutmembuktikanbahwa model pembelajaranpengalamanberbantuan multimedia lebihefektifditerapkandalampemebelajaranmenulisteksnarasi.Berdasarkanujihipotesis (uji t), yaitudiperolehthitung= 2.288 dengan n = 20untuktarafsignifikansi α = 0,05, danttabel = 2.17. Data tersebutmenunjukkanbahwathitung ≥ ttabelatau 2.288 ≥ 2.17, berartiadaperbedaan yang signifikanantarahasilbelajarmenulisteksnarasi yang diberiperlakuandenganhasilbelajar yang tidakdiberiperlakuan model pembelajaranpengalamanberbantuan multimedia.Dengandemikian, model pembelajaranpengalamanberbantuan multimedia lebihefektifdalampembelajaranmenulisteksnarasi. ;---This research was motivated by the low ability to write narrative texts of students at SMPN 44 Bandung. Because in the low ability to write it can be improved by presenting the media as an intermediary. Media assistance is like media, video and text that can help solve problems in the writing process. In this case learning will apply multimedia-assisted learning models to the learning of writing narrative texts. By this, researchers will look at the initial profile of 44 Bandung Junior High School, rolling out the effectiveness of implementing multimedia-assisted information learning models on learning to write narrative texts. The purpose of this study was to see the effectiveness of learning models when multimedia assisted in learning to write narrative texts. This model is one of the learning models that can be used in learning to write narrative texts. The research method is quasi / quasi with nonequivalent control group design. This study uses two classes, namely the control class and the experimental class with a total of 20 people. The data in this study are the results of the test of the ability to write narrative texts. The results showed that there were significant differences in learning to write narrative texts using multimedia assisted experience learning models. This is evidenced by the average score of pre-test and post-test in the control and experiment class. The average score of the pre-test in the experimental class was 63, and the post-test was 70. Unlike the control class, the average score of the pre-test in the control class was 62.3, and the post-test in the control class was 64.4. This data proves that the multimedia assisted experience learning model is more effectively applied in learning to write narrative text. Based on hypothesis testing (t test), which is obtained t count = 2.288 with n = 20 for the significance level α = 0.05, and t table = 2.17. The data shows that t count abel t table or 2.288 ≥ 2.17, meaning that there is a significant difference between the learning outcomes of writing narrative texts that are treated with learning outcomes that are not treated with multimedia assisted experience learning models. Thus, the learning model of multimedia-assisted experiences is more effective in learning to write narrative texts.